ANALYSIS EFFECT OF INFLATION RATES, INTEREST RATES, EXPORTS AND IMPORTS TO VALUE OF CURRENCY EXCHANGE RATE OF RUPIAH AGAINST UNITED STATES DOLLARS 1998 – 2012 - Dayat Hidayat; Ari Usman (Universitas Serang Raya, 2015)
This research aimed to determine the development of the exchange rate, the extent to which Indonesia can repair and recover the economy after the financial crisis of 1998 to the present. The data used in the form of quantitative data, namely exchange rate, inflation rates, interest rates, exports and imports from 1998 to 2012 to process the data used SPSS version 20 and helps by computer. Based on estimates obtained significant value for the inflation of 0,260 or 0,260 > 0.05, this means that the rate of inflation but no significant effect on the exchange rate on the dollar value of the United States in 1998-2012. While the value for the interest rate obtained at 0.963 or 0.963 > 0.05, this means that the interest rate but no significant effect on the exchange rate on the dollar the United States in 1998-2012. As for the value of exports and imports respectively show the figure of 0.174 or 0.174 > 0.05 and 0.123 or 0.123 > 0.05, which means that exports and imports, but no significant effect on the exchange rate on the dollar value of the United States in 1998-2012. Based on calculations, the significant value of 0.112 or 0.112 > 0.05 (5%) which means that independent variables are inflation, interest rates, exports and imports together, but no significant effect on the exchange rate on the dollar value of the United States. R value of 0.705, which means that the correlation between the variables of inflation, interest rates, imports and exports to the exchange rate is equal to 0.705. In this case there is a close relationship since the value of R approaches 1, while the coefficient of determination or R Square (R2) of 0.497, which means the percentage contribution of variables influence inflation, interest rates, imports and exports to the exchange rate on the dollar value of the United States amounted to only 49.7%, while the remaining 51.3% is influenced by other variables not included in this research. Keywords : Financial Crisis, Exchange Rate, Inflation, Interest Rate.